Diastereoselective synthesis of the 5-hydroxy-pyrrolidinone amino acid of the microsclerodermins and model studies for an end-game strategy for microsclerodermin B - Winter, C; Pullin, R; Donohoe, T (Elsevier, 2017)
The first diastereoselective synthesis of the 5-hydroxy-pyrrolidinone amino acid common to eight members of the microsclerodermin family is presented. Our strategy involves formal hydration of an unsaturated precursor via the use of a two-step hydroxybromination-debromination protocol; this procedure provides exclusively the requisite 4,5-cis-pyrrolidinone. Furthermore model studies are presented that indicated the potential viability of this hydration strategy in the context of a synthesis of microsclerodermin B.